2013
DOI: 10.1093/jac/dkt155
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in vivo assessment of drug efficacy against Mycobacterium tuberculosis using an improved firefly luciferase

Abstract: ObjectivesIn vivo experimentation is costly and time-consuming, and presents a major bottleneck in anti-tuberculosis drug development. Conventional methods rely on the enumeration of bacterial colonies, and it can take up to 4 weeks for Mycobacterium tuberculosis to grow on agar plates. Light produced by recombinant bacteria expressing luciferase enzymes can be used as a marker of bacterial load, and disease progression can be easily followed non-invasively in live animals by using the appropriate imaging equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 26 publications
2
58
0
Order By: Relevance
“…One milliliter of Leibovitz's L-15 medium (Gibco Life Technologies) containing 10 6 CFU of either SCHU S4 or SCHU S4-lux was added to cell monolayers to achieve a multiplicity of infection (MOI) of 1. Each strain was added to wells in triplicate for each time point.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One milliliter of Leibovitz's L-15 medium (Gibco Life Technologies) containing 10 6 CFU of either SCHU S4 or SCHU S4-lux was added to cell monolayers to achieve a multiplicity of infection (MOI) of 1. Each strain was added to wells in triplicate for each time point.…”
Section: Methodsmentioning
confidence: 99%
“…Noninvasive imaging techniques, such as bioluminescence imaging (BLI), can report spatial and temporal aspects of infectious diseases in vivo both longitudinally and in real time (9). BLI typically relies on the detection of light produced by luciferase-catalyzed oxidation reactions, which are encoded in the pathogen of interest, by use of a sensitive charge-coupled device (CCD) camera (10). Pivotal experiments by Contag et al have demonstrated the usefulness of BLI in the noninvasive study of bacterial pathogenesis and the evaluation of antibiotic treatments for Salmonella enterica serovar Typhimurium (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…70 Also, in vivo imaging of tuberculosis progression was tried in mice after infection of an M. tuberculosis strain carrying a red-shifted derivative of the firefly luciferase gene. 71 Recently, MRI imaging of S. aureus labeled with iron oxide particle was developed for detection of S. aureus colonies in infection models. 72 However, these methods are not suitable for clinical application because they involve pre-labeled/modified bacteria, where bacteria tracking in animal models were visualized by luminescence and MRI.…”
Section: New Target: Biofilmmentioning
confidence: 99%
“…In addition, new putative targets of atherosclerosis that are non-macrophage-related, such as biofilm and amyloid fibrils, have been suggested as potential targets. Although bacteria/ bacteria film (biofilm) [113][114][115] and amyloid fibrils [69][70][71] are known to be components of atherogenesis, thus far there have been no development of non-invasive imaging techniques that are targeted at either biofilm or amyloid fibrils in the area of atherosclerosis imaging. Thus, it is clinically necessary to develop a non-invasive imaging modality to evaluate biofilm and amyloid load quantitatively, to monitor disease progression and response to treatment.…”
Section: New Probe Developmentmentioning
confidence: 99%